Leaching behaviour of hazardous waste under the impact of different ambient conditions. (May 2017) - Pecorini, Isabella; Baldi, Francesco; Bacchi, Donata; Carnevale, Ennio Antonio; Corti, Andrea
Highlights: The leaching behaviour of waste marked as hazardous partly stabilised is studied. Column and batch tests are performed and their results are compared. The impact of temperature, compaction and acid conditions are tested with column tests. Column results are comparable with batch results in terms of average concentration. Acid environment accelerates the leaching process. Abstract: The overall objective of this study is to provide an improved basis for the assessment of the leaching behaviour of waste marked as hazardous partly stabilised (European waste catalogue code 19 03 04 ∗ ). Four samples of hazardous partly stabilised waste were subjected to two leaching tests: up-flow column tests and batch equilibrium tests. The research was carried out in two directions: the first aims at comparing the results of the two experimental setups while the second aims at assessing the impact of different ambient conditions on the leaching behaviour of waste. Concerning this latter objective the effect of mesophilic temperature, mechanical constraints and acid environment were tested through column percolation tests. Results showed no significant differences between batch and column leaching test outcomes when comparing average concentrations calculated at a liquid to solid ratio of 10:1 l kg −1 TS. Among the tested ambient conditions, the presence of an acid environment (pH = 4.5) accelerated the leaching process resulting in a higher cumulative released quantity measured on the majority of the investigated polluting substances. On the contrary, the effect of temperature and mechanical constraints seemed to not affect the process showing final contents even lower than values found for the standard test. This result was furthermore confirmed by the application of the principal component analysis.